EFEKTIFITAS PEMBELAJARAN KETERAMPILAN SPEAKING DENGAN PENDEKATAN GENRE DI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Slamet, Sri (Jurnal VARIDIKA, 2012)
The purposes of this research are to describe language teaching using genre approach, to describe the problems faced by students and lecturers at Language Center UMS, and to de- scribe the strengths and weaknesses of this approach in which the approach  is compared with a previous  method. This research is a descriptive qualitative research. It uses informant and docu- ment sources. The informants are the students of semester 2 and  the lecturers of Speaking Acqui- sition 2 at UMS. The techniques used in data collecting are by giving questionnaire, doing an in- terview, observing, and giving a test. The result of the research shows that (1) teaching English using genre approach has not been effective yet. The ineffectiveness of this approach is caused by (a) the lecturers, who still do not understand the concept of genre and how to teach it to the stu- dents, (b) the topic of dialogue is not interesting to the students, (c) the exercises of the book are not various, and (d) the students are not well-motivated by the lecturers. (2) Genre approach in teaching English is one of the methods to develop student and lecturer?s activity on speaking abil- ity. (3) The weakness of this approach is that the students are still lack of mastery on vocabulary, grammar and pronunciation. Based on the finding, it is suggested for the policy maker at LC to hold a workshop on teaching Speaking based on genre approach. The materials on workshop should be focused on teaching speaking for a big class, the method on giving the task or assign- ment, and the ways to evaluate it. It is also suggested that the curriculum should cover Reading Subject which can be used to emphasize on students vocabulary, grammar, and pronunciation.